Circulating phagocytes: the ancient and conserved interface between immune and neuroendocrine function. (9th November 2015) - Malagoli, Davide; Mandrioli, Mauro; Tascedda, Fabio; Ottaviani, Enzo
ABSTRACT: Immune and neuroendocrine functions display significant overlap in highly divergent and evolutionarily distant models such as molluscs, crustaceans, insects and mammals. Fundamental players in this crosstalk are professional phagocytes: macrophages in vertebrates and immunocytes in invertebrates. Although they have different developmental origins, macrophages and immunocytes possess comparable functions and differentiate under the control of evolutionarily conserved transcription factors. Macrophages and immunocytes share their pools of receptors, signalling molecules and pathways with neural cells and the neuro‐endocrine system. In crustaceans, adult transdifferentiation of circulating haemocytes into neural cells has been documented recently. In light of developmental, molecular and functional evidence, we propose that the immune–neuroendocrine role of circulating phagocytes pre‐dates the split of protostomian and deuterostomian superphyla and has been conserved during the evolution of the main groups of metazoans.